2007
DOI: 10.1080/00420980701507639
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Location of Home Workers in Montreal, Toronto and Vancouver

Abstract: This study analyses the distribution of home workers across the three largest urban regions in Canada and shows how they differ across sex of home worker, household type, income level, occupation and industry. The highest proportion of home workers is in art, culture and recreation occupations followed by management, the field dominated by men. Women home workers make the financial, secretarial and administrative occupations the third-largest group of home workers. The spatial distribution of home workers foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…us, land use and transportation strategies that are desirable from some perspectives will tend to weaken the motivation to work at home, and conversely, some factors that seem to increase the motivation to work at home are widely viewed as less sustainable. In an independent study that reinforces this point, Moos et al (2006) found that teleworking tended to increase housing consumption (from investing in non-work-related amenities to increase the comfort of spending much more time at home, to furnishing the home office, to adding another room to the residence, to moving to a larger home). Accordingly, these results point to the complexity of trying to nd the right balance among demand management strategies that sometimes act in competition rather than in synergy.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 55%
See 1 more Smart Citation
“…us, land use and transportation strategies that are desirable from some perspectives will tend to weaken the motivation to work at home, and conversely, some factors that seem to increase the motivation to work at home are widely viewed as less sustainable. In an independent study that reinforces this point, Moos et al (2006) found that teleworking tended to increase housing consumption (from investing in non-work-related amenities to increase the comfort of spending much more time at home, to furnishing the home office, to adding another room to the residence, to moving to a larger home). Accordingly, these results point to the complexity of trying to nd the right balance among demand management strategies that sometimes act in competition rather than in synergy.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 55%
“…e impact of the residential built en ironment on work at home adoption and equency Ettema (2010); Moos andSkaburskis (2007, 2008); Muhammad et al (2007aMuhammad et al ( , 2008Muhammad et al ( , 2007b Positive association: Inner city; suburban if the spouse is also a home worker e original database consisted of 8000 addresses but only 6746 addresses turned out to be valid. e number of responses totaled 1682, for a response rate of 24.5 percent.…”
Section: Data Collectionmentioning
confidence: 99%
“…Location analysis of home workers in the United States reveals that they are no more dispersed than the rest of the workforce (Ellen and Hempstead 2002). Contrary, home workers within Canada's largest three cities were found to be more decentralized than commuters with the exception of those in professional occupations (Moos and Skaburskis 2007), and in forthcoming work, it will be shown that this pattern holds at the intermetropolitan level. The Canadian studies remain consistent with findings in the United States because neither found evidence of a completely different location pattern for home workers than commuters, but Canadian findings do point to differences in location tendencies away from the center and major cities for home workers.…”
Section: Residential Locationmentioning
confidence: 89%
“…While an increasing number of employees are engaged in some form of teleworking, finding exact numbers has proven somewhat challenging because it can take many different forms, ranging from the work arrangement described in this paper to homebased 'piece work' and/or work done in satellite offices (Tremblay 2002;Tremblay et al 2006). Definitional and quantification challenges notwithstanding, Moos and Skaburskis (2007) cite estimates of approximately ten per cent of the workforce in the US, Europe and Canada, with expectations of further increases, particularly among professional, technical and middle managers (Johnson et al 2007;Moos/Skaburskis 2007). A recent study of three large Canadian cities (Montreal, Toronto and Vancouver) has reported that 3.9% of employed adults between 15 and 74 years old work at home for pay, representing 6% of the labour force in the respective cities (Moos/Skaburskis 2007).…”
mentioning
confidence: 99%
“…Definitional and quantification challenges notwithstanding, Moos and Skaburskis (2007) cite estimates of approximately ten per cent of the workforce in the US, Europe and Canada, with expectations of further increases, particularly among professional, technical and middle managers (Johnson et al 2007;Moos/Skaburskis 2007). A recent study of three large Canadian cities (Montreal, Toronto and Vancouver) has reported that 3.9% of employed adults between 15 and 74 years old work at home for pay, representing 6% of the labour force in the respective cities (Moos/Skaburskis 2007). According to Moos and Skaburskis, in terms of industry sectors, "business and other services have the largest number of homeworkers followed by finance, insurance and real estate" (2007: 1788).…”
mentioning
confidence: 99%